FORMATION OF THE AESTHETIC CONSCIOUSNESS OF FUTURE GRAPHIC DESIGNERS IN THE DESIGN OF DESIGN OBJECTS BY MEANS OF DIGITAL TECHNOLOGIES - Kostiuk, Olha; Borysova , Svitlana; Bozhynskyi, Nazar; Zinenko , Tetiana; Borysov , Hlib (Revista Prâksis, 2025)
The purpose of the article is to analyse the impact of digital technologies on the formation of aesthetic consciousness of future graphic designers. The study uses a mixed methodology, including quantitative and qualitative phases. The questionnaires collected objective data on aesthetic consciousness, and in-depth interviews allowed us to consider in detail the individual approaches and creative processes of the participants. The sample size is 45 participants representing different levels of experience in graphic design. The results indicate a significant impact of digital technologies on graphic design, including massification and demassification of creation processes, new perspectives for interactive design, and increased mobility in design. The survey found that 85% of participants regularly use digital technologies, mainly Adobe Illustrator. The observations confirmed the importance of self-expression in the creative process, which is reflected in 45% of the participants' creative decisions. The general tendency is high self-awareness and development of the creative process among future graphic designers, which indicates their readiness for independent and expressive creative activity. The conclusions emphasise that modern digital technologies allow future graphic designers to effectively experiment, improve their work and expand their creative capabilities. This approach contributes to the formation of harmony and emotional expressiveness in their creative solutions, marking a new stage in the development of graphic design under the influence of digital innovations.